KORELASI ANALISIS WACANA KRITIS DENGAN KARANGAN BEBAS SISWA KELAS IV MIN 2 SLEMAN YOGYAKARTA - Rizki Maulinisa; Aninditya Sri Nugraheni (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2020)
This study aims to look at the correlation between Critical Discourse Analysis and Free Essays of Class IV MIN 2 Sleman Yogyakarta students. This research uses quantitative research methods. The researcher distributed questionnaires to all grade 4 students because the papulation class did not reach 100 students, so the researchers chose all students to be sampled in this study. Therefore, the population in this study is also a research sample to collect quantitative data. The result of simple correlation analysis obtained the correlation between Critical Discourse Analysis with Free Essay Writing Skills is 0.295. This shows that there is a fairly strong relationship between Critical Discourse Analysis with Essay Writing Skills. While the direction of the relationship is positive because the value of r is positive, it means that the higher the Critical Discourse Analysis, the more the students write essay writing skills.